Microbivalves from the Monte Leon Formation (Early Miocene), Patagonia, Argentina - Griffin, Miguel; Pastorino, Roberto Santiago Guido
Three new species (Mysella donaciformis n. sp., Cosa helianthea n. sp., and Lissarca saraballentae n. sp.) of small bivalves are described from early Miocene rocks in southern Patagonia. The outcrops lie along the coast of the province of Santa Cruz, within the boundaries of the Monte León National Park. The fossil-rich rocks exposed there at the base of the coastal cliff are included in the Punta Entrada Member of the Monte León Formation. This stratigraphic unit has been dated as early Miocene. It was probably deposited in a tidally-influenced near-shore and fully marine environment. The affinities of these small mollusks lie with taxa known to occur in other areas of the Southern Ocean, such as Antarctica, Australia, and New Zealand. The dispersal of these mollusks across vast expanses of water by means of rafting on drifting kelp is discussed. Fil: Griffin, Miguel. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Pastorino, Roberto Santiago Guido. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina